Strengthening religious moderation based on local wisdom haikalima henaluaka in manipa island - Ali Litiloly (Balai Diklat Keagamaan Ambon, 2025)
This study aims to find out about the strengthening of religious moderation based on the local wisdom of Haikalima Henaluaka on Manipa Island, with the focus of the survey of the local wisdom of Haikalima Henaluaka which has a relationship with religion and how the local wisdom of Haikalima Henaluaka strengthens religious moderation. This study is qualitative and uses descriptive analysis techniques. This study found that the values ​​of the local wisdom of Haikalima Henaluaka have a relationship with religious values; this is because the local wisdom of Haikalima Henaluaka is inspired by spiritual values ​​, which are used as guidelines for values ​​in the social life of the community on Manipa Island without distinguishing between people's backgrounds. From the Islamic perspective, the local wisdom of Haikalima Henaluaka is the same as the term Urf (custom), and it has become a tradition that does not conflict with religion. The local wisdom values ​​of Haikalima Henaluaka can realize religious moderation in the communities of the seven countries on the island of Manipa because these local wisdom values ​​can unite two groups of people whose lives are spread separately in one coastal area and live side by side and create cooperative relationships and maintain harmonious interactions in all countries with different ethnicities, cultures, languages ​​, and religions on the island of Manipa.